Fashion designers' attitude-behaviour inconsistencies towards a sustainable business model: a neutralisation theory perspective - Muposhi, Asphat; Nyagadza, Brighton; Mafini, Chengedzai (Emerald, 2022)
Purpose Fashion designers in South Africa remain ambivalent in embracing sustainable fashion. This study examines the role of neutralisation techniques on attitude towards sustainable fashion. The study was conducted in South Africa, an emerging market known for water scarcity and pollution emanating from the textile industry.